Paradygmat krajowego, instytucjonalnego zaangażowania misyjnego na podstawie działalności Prokury Misyjnej Misjonarzy Oblatów Maryi Niepokalanej (1969-2022) - Wrzos, Marcin Jan (Annales Missiologici Posnanienses, 2023)
The Missionary Procuration of the Missionary Oblates of Mary Immaculate (1969-2022) is a national institution supporting Oblate, but not only, missionary activity ad gentes. Its structure also includes: Public Association of the Faithful “Friends of the Oblate Missions” (since 1969), Association Oblacka Pomoc Misjom “Lumen Caritatis” (since 2009), the Missionary Roads magazine and website (since 2014), and the Mazenodianum Institute Foundation (since 2021). These institutions, apart from the association of “Friends of the Oblate Missions”, previously operated separately. From the very beginning, the Missionary Procuration has been associated with the basic areas of its activity: providing spiritual and material assistance to missionaries and the works they carry out; supporting the awakening of missionary vocations; propagating the missionary idea both among the clergy and lay people, also through: the activities of the Friends of the Mission, the activities of the “Lumen Caritatis” association, the publishing of the “Missionary Roads” magazine, the www.misacyjne.pl website, books and ephemeral publications, presence in other social media, parish animations and mission retreats, conducting social campaigns, other evangelistic, cultural and scientific events related to the promotion of Oblate missions. The conducted research shows, among others, that: this activity in many of its aspects may be paradigmatic for other national mission institutions (eg WYD or the missionary secretariat of the Divine Word Missionaries work in a similar way). The realities of missionary activity and research have also shown that the centralization of missionary activities in one institutional entity within the religious or diocesan jurisdiction is a better solution than their atomization. The purpose of missionary institutions is not only spiritual and material help for the mission, but also a much wider multifaceted activity; in the activities of ecclesial missionary institutions, both proven and modern missionary tools should be used, and in-depth mission formation, as well as the creation of communities, groups of people engaged in mission is a condition of permanent missionary assistance.